Moving Towards an Indigenous Research Process: A Reflexive Approach to Empirical Work With First Nations Communities in Canada - Toombs, Elaine; Drawson, Alexandra S; Chambers, Lori; Bobinski, Tina L. R.; Dixon, John; Mushquash, Christopher J. (International Indigenous Policy Journal, 2019)
Moving towards reconciliation within Indigenous research requires the careful examination of existing practices at all stages of the research process. Engagement in and dissemination of reflexive processes may increase the relevance of research results for Indigenous communities and partners. This article describes and contextualizes the results obtained from this qualitative research study examining parenting needs and child reunification in these communities. The initial results were deemed relevant by the partnering community but research stakeholders reported that they did not reflect all community values. Based on the advice of the Research Advisory Group, the research team decided to further analyze the results to address these shortcomings. The reanalysis process focused on improving the perceived meaningfulness and relevance to communities. Exploration of how these results were re-situated in an Indigenous framework of wellbeing is discussed. Researcher reflections about the project processes and considerations for future research are explored.